Attitude toward patients with mental disorders: what is going on amongst Iranian pharmacies? - Fatemeh Shirvaniyan; Negin Eissazade; Seved Vahid Shariat; Noushin Khademoreza; Masoomeh Daneshvar; Mohammadreza Shalbafan (BMC Psychology, 2024)
Abstract Introduction As the incidence of mental disorders continues to rise, and pharmacy staff can significantly affect the willingness of patients with mental disorders to seek help; we aimed to evaluate the stigmatizing attitude of the pharmacy staff toward these patients in Iran. Methods We conducted this cross-sectional study between April 2020 and December 2021 in Tehran, Iran, and included pharmacists, pharmacy technicians and pharmacy students, with the experience of working in a pharmacy for at least three months. The social distance scale (SDS) and dangerousness scale (DS) were used to measure the stigmatizing attitude of the participants. Higher scores indicated more stigmatizing attitudes. Results We included a total of 186 participants with a mean age of 32.97 ± 9.41 years, of which 101 (54.3%) were male, and 75 (40.3%) were pharmacists, 101 (54.3%) were pharmacy technicians, and 8 (4.3%) were pharmacy students. The mean SDS score was 14.2 ± 4.13, and the mean DS score was 33.85 ± 8.92. The greatest tendency for social distance was reported for a patient with a mental disorder, ‘being the caretaker of their children for an hour or two’ and ‘marrying their children.’ The most perceived dangerousness was reported for a patient with a mental disorder ‘owning a gun.’ Positive personal history of psychopharmacological treatment was statistically correlated with lower DS (P = 0.001) and SDS (P = 0.007) scores. Positive family history of psychiatric inpatient admission was significantly correlated with higher DS (P = 0.05) and SDS (P = 0.03) scores. Higher rates of ‘received psychiatric prescriptions per month’ was associated with lower DS scores (P = 0.04). Conclusion Our participants did not have an overall positive attitude toward patients with mental disorders. Although, compared to previous studies, they held a more positive attitude. Positive personal history of psychopharmacological treatment predicted a more positive attitude and positive family history of psychiatric inpatient admission predicted a more negative attitude.